Leitores competentes na Literatura - SARAIVA, Michelle Nascimento (2019)
This paper aims to show a way of working so that we can have competent students in reading and so that they can understand what they read. In addition, it shows students that reading can transform the way they see and live in an increasingly competitive and demanding society, indicating that reading can make us travel and know places without leaving our own place. In this paper, we present a didactic sequence on the sub gender myth, which was performed at the Municipal School of Basic Education Industrial District in the Barcarena municipality, where we will show how to lead our students to understand the characteristics of the myth and to understand what they read, besides taking them to the production of a myth of knowledge of themselves, to prove that reading is not simply decoding letters, but rather, it is associated with the knowledge that students already have and the experiences they already had.